D9.16 Report on Social Responsibility Activities - Papoutsa, Christiana; Hadjimitsis, Diofantos G.; Theocharidis, Christos; Pekri, Marina; Loulli, Eleni; Prodromou, Maria; Komodromos, George; Tziortzis, Stelios (My University, 2022)
This deliverable provides an overview of the social responsibility activities that have been conducted through seminars, webinars, lectures and activities related to the 12 thematic research areas. The objective of the activities is to inform and engage with the wider public regarding the beneficial impact of the research conducted in the ECoE for the environment, the society and the economy. This is done through open lectures and activities on a range of topics including food security, sustainable agriculture and forestry, marine and maritime and inland water research, air quality monitoring, climate change, disaster risk reduction, cultural heritage, resource efficiency and raw materials, secure clean and efficient energy, Big Earth data analytics as well as geo-informatics. The social outreach component to inform the public regarding the usefulness of Earth observation data was stipulated in several of the Letters of Support and Letters of Commitment for the EXCELSIOR project.
Keywords: Remote Sensing; EXCELSIOR; ERATOSTHENES Centre of Excellence; Earth Observation